PENERAPAN METODE PEMBELAJARAN UNTUK MENINGKATKAN PRESTASI BELAJAR PAI SISWA - Suprihatin; Ratika Novianti; Nur Widiastuti (NURHIDAYAH: Jurnal Ilmu Pendidikan, 2024)
This type of research is descriptive qualitative with the research location being SDIKT Robbi Rodhiya Bandar Lampung. The data collection methods used are observation, interviews and documentation. The data analysis technique is qualitative descriptive analysis, namely data reduction, presentation and drawing conclusions. The research results showed that the learning achievement of Islamic Religious Education at SDIKT Robbi Rodhiya Bandar Lampung was optimal. This can be seen from the very satisfactory learning achievement of the students after an evaluation was held. There are several methods used by educators to apply effective learning methods, namely: (a) looking at class conditions, (b) looking at the students' condition, (c) adapting the method to the learning material. This research has implications for educational institutions which are expected to be able to further optimize the learning achievements of their students, especially in Islamic Religious Education subjects, such as holding additional learning specifically for Islamic Religious Education subjects or in other ways. other. Educators are expected to be able to master and apply learning methods effectively.